(untitled) (World Bulletin of Public Health, 2023)
Chronic liver diseases have recently occupied the leading place as the most common cause of mortality in many developed countries. One of the manifestations caused by liver failure is hepatic encephalopathy syndrome, which is a disorder of brain function that manifests itself in a wide range of neurological or psychiatric disorders from minimal cognitive impairment to coma. Researchers have found evidence that the use of proton pump inhibitors (PPIs) may cause changes in gut bacteria that may contribute to liver disease and, when pathogenic bacteria multiply in the intestines, may cause hepatic encephalopathy and/or worsen the stage.